Preparasi Teofilin dalam Pembawa Vesikular Etosom untuk Penggunaan Transdermal - Akib, Nur Illiyyin; Ritonga, Halimatussadiyah; Mahfuz, Muhammad (Pharmauho: Jurnal Farmasi, Sains, dan Kesehatan, 2019)
Theophylline is a methyl xanthine of alkaloid derivative compound has been used as a bronchodilator in the treatment of chronic lung disorders, especially asthma. Oral administration of theophylline causes inconvenient for patients including bitter taste, narrow therapeutic range, and indigestion due to increased of gastric acid secretion. Therefore, other administration of theophylline has been developed as transdermal delivery system. This study disscused about preparation of theophylline in ethosome as vesicular carrier. Preparation of ethosome was used hot method (40oC) and cool method (30oC). Characterization of ethosomes includes observation of shape and size of vesicles by microscopic method and the vesicles were fractionated by centrifugation then entrapment efficiency (% EE) were measured by spectrophotometric method. Then optimazed theophylline that entrapped in ethosome. Based on the results, ethosomes preparation by hot method were produced Small Unilamellar Vesicle (SUV), the size were 0,0522-0,100 Âµm, and the highest value of % EE was 98.95%, while ethosomes preparation by cold method were produced Small Unilamellar Vesicle (SUV), the size were 0.0522-0.100 Î¼m, and the highest value of % EE was 99.80%. The optimum concentration of theophylline was entrapped in etosom was 0.1%. It was concluded that cold method was the appropriate method for preparation of theophylline in ethosome as vesicular carrier.Keywords: Etosome, theophylline, vesicular, transdermal